Correlative Imaging and super resolution microscopy studies reveal complexities in determining live-dead state of bacteria - Jiaqi Luo; Rasmita Raval (Biofilm)
Imaging techniques are widely used to determine the physiological state of bacterial cells and provide an important platform for antibacterial evaluation in biofilms research. The commercial counter-staining SYTO 9 – propidium iodine kit is a popular choice for viability studies, with cell membrane damage due to antimicrobial action leading to replacement of the SYTO 9 dye with propidium iodine. This study investigates the live-dead state of cells in early-stage Staphylococcus aureus biofilms using correlative Fluorescence Microscopy (FM), Scanning Electron Microscopy (SEM) and super resolution Structural Illumination Microscopy (SIM). Correlative imaging data obtained at the single-cell level show that the physiological states of individual bacterial cells indicated by the SYTO 9 – propidium iodine counterstain in FM does not correlate directly with the detailed cell morphology observed by SEM. In addition, SIM was used to map sub-cellular distributions of SYTO 9 – propidium iodine dyes within single cells and revealed greater complexity than hitherto assumed, with 4 different cell-states identified, including double-stained ones and those where SYTO-9 is bound to substances at the cell perimeter. With this knowledge, we present ternary plots to illustrate the significant impacts of this complex staining behaviour on underestimation of cell-membrane damage due to antimicrobial actions and, thus, overestimation of bacterial survival rate in biofilms research.